Kunxian capsule alleviates podocyte injury and proteinuria by inactivating β-catenin in db/db mice - Jin, Bo; Liu, Jing; Zhu, Yan; Lu, Jian; Zhang, Qingyan; Liang, Yan; Shao, Qiuyuan; Jiang, Chunming (Frontiers in Medicine, 2023)
Background Diabetic kidney disease (DKD) remains the primary cause of end-stage renal disease (ESRD) globally, but treatment options are limited. Kunxian capsule (KXC) has been utilized for the treatment of autoimmune diseases and IgA nephropathy in China. However, its effect on DKD remains poorly investigated. Therefore, this study aimed to explore the protective effect of KXC in db/db mice and elucidate its underlying mechanism. Methods The renoprotective effects of KXC were assessed in a DKD mouse model using male BKS db/db diabetic mice. After 8 weeks of treatment, the urinary albumin-to-creatinine ratio (UACR), blood biochemical parameters, renal histopathological manifestation, and podocyte ultrastructural changes were evaluated. Additionally, the expression of podocyte epithelial-to-mesenchymal transition (EMT) markers [WT1, ZO-1, and collogen I (Col1a1)] was quantitatively analyzed. Furthermore, we explored the role of KXC in the β-catenin signaling pathway to elucidate the underlying mechanism of KXC’s renoprotective effect. Results KXC treatment effectively reduced albuminuria and attenuated renal structural abnormalities in db/db mice. Additionally, KXC restored the protein and mRNA expression of WT1 and ZO-1 while suppressing the expression of Col1a1 in db/db mice, indicating its ability to alleviate podocyte EMT. Mechanistically, KXC exerted a significant suppressive effect on the activation of β-catenin signaling in diabetic kidneys. Conclusion KXC has the potential to protect podocytes during DKD by alleviating podocyte EMT through inactivating β-catenin signaling.